Pemberdayaan Kreativitas Anak melalui Pelatihan Ecoprint pada Totebag Berbasis Potensi Alam Lokal di Bimbel Arsal, Desa Tolokan - Anis Muflihah; Daud Rismana; ‘Aliyatus Sholihah Amaniyyah; Ummu Zahrotun Ni'mah; Rahma Arsyalaila; Aulia Sabani; Devina Ananda Sabila; M. Daffa Nail Nashif; Annisa Eka Paramitha; Alfina Nur Hidayah; Fadila Sita Pramesti; Siti Rohana; Putri Wulan Ramadhani; Briliant Faizal Junior; Laila Azzahro; Mutiara Sukmaningrum (Jurnal Pengabdian Masyarakat Waradin, 2025)
This community service research aimed to empower elementary school children’s creativity through fun, educational, and environmentally friendly activities. Conducted at Bimbel Arsal in Tolokan Village, the project focused on ecoprinting training on tote bags using local natural resources. The activity followed a three-stage implementation process: preparation, execution, and reflection. The preparation stage included coordination with tutoring teachers and the gathering of tools and materials. During the execution stage, children were introduced to ecoprinting and practiced the pounding technique with guidance from the KKN team. The reflection stage involved discussions, a question-and-answer session, and product evaluation. The results showed that the children successfully learned ecoprinting techniques, understood the environmental benefits, and expressed their creativity through unique and beautiful ecoprint designs on tote bags. Although challenges arose—such as difficulties selecting natural materials with strong color yields and technical issues during the beating process—the activity proceeded smoothly, thanks to the children’s enthusiasm, support from the tutoring center, and careful planning. Ultimately, the project proved effective in enhancing the children’s creativity, self-confidence, and environmental awareness. This activity not only empowered children but also contributed to promoting sustainable practices and fostering environmental consciousness among young learners. The success of the program highlights the importance of creative, hands-on learning activities in promoting both personal development and environmental responsibility.